2018
DOI: 10.5582/bst.2018.01083
|View full text |Cite
|
Sign up to set email alerts
|

Expression of glucocorticoid receptor shows negative correlation with human B-cell engraftment in PBMC-transplanted NOGhIL-4-Tg mice

Abstract: The humanized mouse system is a promising tool for analyzing human immune responses in vivo. Recently, we developed a new humanized mouse system using the severely immunodeficient NOD/Shi-scid-IL2rγ (NOG)-hIL-4-Tg mouse, which enabled us to evaluate the human humoral immune response after peripheral blood mononuclear cell (PBMC) transplantation. However, the mechanism by which hIL-4 enhances antigen-specific IgG production in these mice is not clear. In this study, we analyzed the relationship between human ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…The humanized mouse model is a powerful tool for the comparison of human immunity 27 , 28 as the engraftment of peripheral blood (PB) cells derived from patients recapitulates their conditions 29 . We developed a second-generation humanized mouse model, hu-PBL hIL-4 NOG mouse, to assess PBMC-mediated humoral immune response in vivo 12 , 30 . This mouse strain was based on a severely immunodeficient NOD/Shi-scid IL2rγnull (NOG) mouse and expressed human IL-4.…”
Section: Introductionmentioning
confidence: 99%
“…The humanized mouse model is a powerful tool for the comparison of human immunity 27 , 28 as the engraftment of peripheral blood (PB) cells derived from patients recapitulates their conditions 29 . We developed a second-generation humanized mouse model, hu-PBL hIL-4 NOG mouse, to assess PBMC-mediated humoral immune response in vivo 12 , 30 . This mouse strain was based on a severely immunodeficient NOD/Shi-scid IL2rγnull (NOG) mouse and expressed human IL-4.…”
Section: Introductionmentioning
confidence: 99%
“…The HLA haplotype of donor PBMC might not be relevant to the ability of an antibody secretion after immunization. The reason why NOG-hIL-4-Tg retain B cells and succeeded in the specific antibody production was examined, and we found that the engrafted human lymphocytes decreased glucocorticoid receptor expression, which dampens the humoral immunity [138].…”
Section: Humanized Mouse System To Evaluate Antigen-specific Antibodymentioning
confidence: 98%
“…The humanized mouse model is a powerful tool for the comparison of human immunity 27,28 as the engraftment of peripheral blood (PB) cells derived from patients recapitulates their conditions 29 . We developed a secondgeneration humanized mouse model, hu-PBL hIL-4 NOG mouse, to assess PBMC-mediated humoral immune response in vivo 12,30 . This mouse strain was based on a severely immunode cient NOG mouse and expressed human IL-4.…”
mentioning
confidence: 99%